PERILAKU MENYIMPANG PENGGUNA INSTAGRAM DI KOTA MAKASSAR (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study discusses the type of deviant behaviors mostly happening in Makassar City, South Sulawesi, Indonesia, as a psychological side effect of social media. This research’s objectives are to reveal the deviant behaviors of Instagram users live in Makassar City, which focused on; What type of deviant behaviors and what motivates the Instagram user to do their deviant acts. Using the sociological approach, the main sources of data of this research are five Instagram users with deviant behavior who is currently live in Makassar city. This research data were collected through observation, interviews, and documentation study.  Data processing and analysis techniques, namely through the process of data reduction, data presentation, drawing conclusions, and verification. The results showed that the type of deviant behavior mostly happens to Instagram user specifically teenager are alcohol addiction and abnormal sexual behavior (LGBT). The motivation of doing such deviant acts mostly coming from the inner self, family issues, bad social environment, past experiences, and the psychological side effect of social media.